SIFAT VENIR DAN KAYU LAPIS ENAM JENIS KAYU DARI IRIAN JAYA - M I Iskandar; Suwandi Kliwon; Paribntro Sutigno (Jurnal Penelitian Hasil Hutan, 1989)
A  study   result on  the  suitability  of  wood  species  from  Irian Jaya as raw material for veneer and plywood  is reported  in this paper.  This  study   consisted  log  peeling  characteristic,  veneer  property,  some physical  and mechanical properties of  plywood   (triplex  and multiplex).All  of  the  logs from  6 wood  species  could  be peeled  in cold  condition, producing 1.5   mm veneer at a cutting  angle between   920-92°30-The  average shrinkage  of  veneer  is  7.99%,    with  a  minimum of  6. 74% (sehiega) and  maximum   of  9. 71 %  (petuon).  Veneer  swelling from oven-dry  to air-dry  condition varied between   2. 68% (katulampa)  and 4.01 % (petuon)  with  an   average  of 3.19%.The  bonding  strength  of plywood   for  type  11  from  6 wood  species  (100%)  conform's  with  the Indonesian  Standard6 wood species  (100%)  with Japanese Standard  and 6 species  (100%)  with German Standard.The specific  gravity  of   multiplex    is  higher  than  triplex.  Some  mechanical  properties of  multiplex are higher  than triplex